Quantitative GABA magnetic resonance spectroscopy as a measure of motor learning function in the motor cortex after subarachnoid hemorrhage - Sugita, Kenji; Anan, Mitsuhiro; Matsuta, Hiroyuki; Shimomura, Tsuyoshi; Fudaba, Hirotaka; Hata, Nobuhiro; Fujiki, Minoru (Frontiers in Neurology, 2023)
The neural mechanisms underlying gross and fine motor dysfunction after subarachnoid hemorrhage (SAH) remain unknown. The γ-aminobutyric acid (GABA) deficit hypothesis proposes that reduced neuronal GABA concentrations and the subsequent lack of GABA-mediated inhibition cause motor impairment after SAH. This study aimed to explore the correlation between GABA levels and a behavioral measure of motor performance in patients with SAH. Motor cortical GABA levels were assessed in 40 patients with SAH and 10 age-matched healthy controls using proton magnetic resonance spectroscopy. The GABA and N-acetylasparate (NAA) ratio was measured in the normal gray matter within the primary motor cortex. The relationship between GABA concentration and hand-motor performance was also evaluated. Results showed significantly lower GABA levels in patients with SAH's left motor cortex than in controls (GABA/NAA ratio: 0.282 ± 0.085 vs. 0.341 ± 0.031, respectively; p = 0.041). Reaction times (RTs), a behavioral measure of motor performance potentially dependent on GABAergic synaptic transmission, were significantly longer in patients than in controls (936.8 ± 303.8 vs. 440.2 ± 67.3 ms, respectively; p < 0.001). Moreover, motor cortical GABA levels and RTs exhibited a significant positive linear correlation among patients (r = 0.572, rs = 0.327, p = 0.0001). Therefore, a decrease in GABA levels in the primary motor cortex after SAH may lead to impaired cortical inhibition of neuronal function and indicates that GABA-mediated synaptic transmission in the motor cortex is critical for RT.